(untitled) (Research, Society and Development, 2020)
In the northeastern semi-arid region, the conditions for breeding horses for reproductive purposes and for the practice of vaquejada must be understood in order to correct limiting factors and adopt measures that maximize the quality of the products. In these conditions, the objective of this work was to characterize the management practices and the reproductive performance of crossbred and PO horses of the Quarter Horse breed in stud farms located in the states of PB, PE and RN. 399 crossbred mares and PO of the Quarter Horses were evaluated for nutritional, health management and reproductive efficiency indexes such as: pregnancy rate (TP), embryo recovery rate (TR), birth rate (TN) and rate service (TS). Of this total, 47 Quarter Horses PO mares were evaluated for age at first calf (IPC), interval between births (IEP), number of births (NC). The values of the variables between the groups were submitted to the Chi-square test. The IPC and IEP data were subjected to analysis of variance followed by the Tukey test. There was no difference (p <0.05) in TP, which ranged from 59.3% to 94.3%, nor in RT, which ranged from 33.3 to 72.7%. TS varied from 62.1-89.7% for animals in confinement and 69.8-93.7% for semi-confined animals. IPC ranged from 44 months to 118 months and was influenced by the year of delivery (P<0,05). The IEP ranged from 12 to 20 months and the NC ranged from 11 to 28 births. It is concluded that the reproductive performance in the evaluated region is satisfactory for the studied species.